THE EFFECT OF AUDIO-VISUAL EXPOSURE (YOUTUBE) TOWARDS LEARNERS’ SPEAKING SKILL - Maulana Sigit Purwa H; Lasim Muzammil (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2019)
This research is intended to investigate how significant the effectiveness of AVE in which YouTube as the platform adopted being compared to the use of another media, i.e. Audio-Picture Series Exposure towards learners’ speaking skill. In order to achieve the purposes of the study, this study entails subjects taken from the population of SMK Budi Mulya Pakisaji by selecting 20 samples and 18 samples for control and experimental group respectively in which the former group was taught using Audio-Picture Series Exposure, while the latter one using AVE (YouTube). The researcher provided similar treatment and topic during the implementation of each exposure. The results show that both groups proved major improvement. Despite the performance improvement, since the result of independent sample t-test was 0.379, it attests that the difference between the groups was insignificant as the result was higher than the significance level set at .05. Such insignificance was apparently posed by some probable factors such as how the control group provide the same effective impact during the lesson, and also caused by the probable limitation as for adopting the availability of apt videos attributed to the selected topic which culminated in over reusing the similar contents. All in all, this study is expected to be contributive and propitious for the teachers and learners as for delivering insights of determining the use of the most suitable media for learning activity. It is also hoped that further research could present more detailed and provide more reliably advantageous findings.